Quantum Machine Learning, Edge AI, Ethical AI, and Autonomous Systems in Smart Cities of Maharashtra - Syed Akhter Hussain (International Journal of Intelligent Systems and Applications in Engineering, 2024)
This paper examines the convergence of Quantum Machine Learning (QML), Edge Artificial Intelligence (Edge AI), and Ethical AI frameworks within the evolving ecosystem of smart cities and autonomous vehicles. Drawing upon data and implementation insights from Maharashtra’s Smart Cities Mission (2023–24), the study analyzes how advanced computational paradigms are reshaping urban governance, intelligent transportation systems, and sustainable infrastructure. QML leverages quantum computing principles such as superposition and entanglement to process complex urban datasets, optimize traffic flow, and enhance predictive analytics beyond classical limitations. Simultaneously, Edge AI enables decentralized, low-latency data processing at the device level important for autonomous vehicles, smart surveillance, and IoT-enabled public services thereby reducing bandwidth dependency and improving real-time responsiveness. The research further emphasizes the importance of ethical AI principles, including fairness, transparency, accountability, privacy protection, and algorithmic explainability, in large-scale public deployments. In the context of urban mobility and digital governance, ethical oversight mitigates risks related to data bias, surveillance overreach, and unequal access to technological benefits. Case observations from Maharashtra indicate measurable improvements in traffic management, energy efficiency, and citizen service delivery through AI-driven decision support systems. The study proposes a scalable, resilient, and human-centric model for next-generation smart cities by integrating QML’s computational acceleration with Edge AI’s real-time adaptability under an ethical governance framework. The findings highlight that technological innovation must be aligned with responsible policy frameworks to ensure inclusive growth, sustainable mobility, and trustworthy AI ecosystems.